Pengaruh Stres Kerja Terhadap Kepuasan Kerja Karyawan Universitas Andalas Dalam Rangka Menerapkan pengelolaan Keuangan badan Layanan Umum (BLU) - Siska, Adilla Juita (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2012)
This study aims to obtain empirical evidence of the influence of work stressed n job satisfaction of employees Andalas University in order to implement the financial management of Public Service Board (BLU). To perform the testing stages of data used 284 employees at the University Andalas Padang. The process of data collection is done by using the observation that involved researchs directly. The research data used are the primary data that sought to spread the research questionnaire to the respondent who has met the criteria of sampling. Within this study there is one types of variable used that is independent of work stressed. Second is the dependent variable is job satisfaction. The process of hypothesis testing is done by quantitative methods. The model used is simple linier regression. Based on test result found that work stressed had no significant effect on job satisfaction of employees Andalas University in order to implement the financial management of Public Service Board (BLU).